Research on the balanced, coordinated and sustainable development of China manufacturing industry. - Weiwei Zhu; Guozhuo Yang (PLoS ONE)
China's manufacturing industry faces the multiple goals of balanced, coordinated and sustainable development. This paper clarifies the connotation of balanced, coordinated and sustainable development of the manufacturing industry from regional structure, industrial structure and development structure. The level of balanced, coordinated and sustainable development of the manufacturing industry is measured using various methods such as index construction model, coupled coordination model and objective assignment method. The temporal and spatial evolution characteristics of the balanced, coordinated and sustainable development of the manufacturing industry are analysed. The following conclusions were obtained: the overall level of manufacturing equilibrium in the east is high, and the level of manufacturing equilibrium in the west and northeast is low. Therefore, it is necessary to promote the level of manufacturing development in the central and western regions through industrial transfer and other means. The overall coordination level of manufacturing industry shows a clear upward trend. The coordination level of manufacturing industry in the east ranks first among the four regions, and the coordination level of manufacturing industry in the west has made the most obvious progress. The overall level of sustainable development of the manufacturing industry is on an upward trend, with the highest level of sustainable development of the manufacturing industry in the east and a relatively low level of sustainable development in the west. There is a need to achieve sustainable development of the manufacturing industry by promoting the integration and development of the digital economy and the manufacturing industry.